Equal Legal Standing of Citizens in Judicial Review of Constitutional Court Law: A Multicultural Perspective to Achieve Legal Certainty - Subhan, Ahmad; Rato, Dominikus; Anggono, Bayu Dwi (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
The phrase of Indonesian citizen that quotes in Article 51 Paragraph 1 of Law Number 8 of 2011 about the Constitutional Court provides the widest possible opportunity for the Indonesian people to contest their rights. A Constitutional Court’s judge as an Indonesian citizen has the same rights in filing a lawsuit regarding his legal interests related to the review of the Constitutional Court Law. This study contains two results. First, the right to file a petition is the right to file a lawsuit or petition to the Constitutional Court. However, in reviewing Legal Certainty in the second discussion, a Constitutional Court judge should be prohibited from reviewing the Constitutional Court Law as it violates Legal Principles, that a Judge cannot be a Judge for himself. From a multicultural perspective, every Indonesian citizen regardless of ethnic, religious or gender background has equal rights to file a judicial review petition to the Constitutional Court. This reflects the spirit of unity in diversity and equality contained in the 1945 Constitution. However, there still needs to be restrictions to avoid conflicts of interest. By upholding the principles of legal certainty and justice, the Indonesian judiciary system can realize the noble ideals of the nation..